Implicações socioambientais da construção de um parque eólico no município de Rio de Fogo-RN - Improta, Rafaella Lenoir (2008)
The purpose of this study was to investigate the social-environmental implications of the first large scale wind farm recently built in Brazil (2006), Parque Eólico de Rio do Fogo (PERF), to the nearby communities. The research was base on the adjustment of the DIS/BCN tool to analyze social impact and it was linked to the multi-method approach. Applying the autophotography strategy, cameras were given to five children from the district of Zumbi, the nearest location to PERF, and they were asked to individually photograph the six places they liked the most and the six places they liked the least in their community. Then, these children were interviewed individually and collectively about the photographs. Adult locals in Zumbi, residents of Zumbi/Rio do Fogo settlement, members of the State and Municipal government and representatives of the PERF were also interviewed with the aid of some of the pictures taken by the children and others that might trigger something to say, as a strategy called sample function. The five children presented positive image towards PERF; all of them chose to photograph it as one of places they liked. Adult population of Zumbi presented positive visual evaluation towards PERF. A small number of the interviewees were aware of the environmental and social benefits of wind energy production. Residents did not participate of the decision making process regarding PERF. They approved the project, especially because of the jobs provided during construction. Nowadays, PERF is something apart from their lives because it no longer provides jobs or any other interaction between the facility and the locals. Residents relate to the land, not with the facility. However, there is no evidence of rejection towards PERF, it is simply seen as something neutral to their lives. The low levels of education, traditional lack of social commitment and citizenship, and the experience accumulated by PERF´s planners and builders in other countries, may be contributing points to the fact that Zumbi residents did not oppose to PERF. It is clear that the country needs a legislation which seriously considers the psycho-social dimension involved in the implementation of wind farms